The THE INFLUENCE OF SOCIAL MEDIA MARKETING ON DECISIONS TO PURCHASE LA MORINGA PRODUCTS STUDY ON INSTAGRAM FOLLOWERS @la_moringantt - Fanggidae, Ronald; Kurniawati, Merlyn; Tulle, Resha Meilefiana (Proceeding of International Management Conference and Progressive Papers, 2024)
The advances of information technology and internet are currently changing in various societal activities including business activities. This forms a society or digital community to meet their needs for goods and services. Promotion via the internet, especially social media, is an advantage or what is known as Social Media Marketing, this is very familiar among business people. This study aims to determine the effect of Social Media Marketing on purchasing decisions for La Moringa products. The variables in this study are Social Media Marketing and Purchase Decisions. This research uses quantitative methods. This research is a descriptive and associative study using a simple linear regression model. By carrying out this procedure, the researcher used a probability sampling technique with the accidental sampling method. To process the data, the researchers carried out several procedures through online questionnaires via Google form to 98 respondents with 28 statement items. In analyzing the data, researchers used descriptive and associative analysis, tested research instruments, tested classical assumptions, and tested hypotheses. The results showed that the effect of Social Media Marketing via Instagram on the Purchase Decision of La Moringa products was 74.8%. Based on the results of testing the hypothesis in this study, it shows that the Social Media Marketing variable with four indicators, namely Content Creation, Content Sharing, Connecting, and Community Building has a significant effect on the Purchasing Decision variable.